2002
DOI: 10.1046/j.1365-2516.2002.00686.x
|View full text |Cite
|
Sign up to set email alerts
|

Paradoxical hyperfibrinolysis is associated with a more intensely haemorrhagic phenotype in severe congenital haemophilia

Abstract: To elucidate potential causes for differing bleeding phenotypes of haemophilic patients of identical degree of coagulation factor deficiency, we investigated 21 male patients with severe haemophilia. Median annual coagulation factor demand and the extent of haemophilic arthropathy were used to discriminate between intensely and less intensely haemorrhagic phenotypes. Haemophiliacs with a median annual coagulation factor demand of 800 IU per kg bodyweight or more and with three or more joints affected by haemop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
61
2
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(66 citation statements)
references
References 32 publications
1
61
2
2
Order By: Relevance
“…The precise analysis of thrombolysis rate provided by the method presented in this paper could effectively upgrade this guidance therapy approach. It could potentially help to estimate altered fibrinolysis in several other pertinent clinical situations such as liver or bone marrow transplantation, liver cirrhosis, and haemophilia, or to assess the haemorrhagic risk after thrombolytic therapy 47–50 . The assay has an intra-assay coefficient of variation of 5.15% which is similar to that reported for the thromboelastrography methods 41, 51 (3 to 6%), but higher than that for the optimised ECLT assay 13, 44 (0.7 to 2.6%).…”
Section: Discussionmentioning
confidence: 99%
“…The precise analysis of thrombolysis rate provided by the method presented in this paper could effectively upgrade this guidance therapy approach. It could potentially help to estimate altered fibrinolysis in several other pertinent clinical situations such as liver or bone marrow transplantation, liver cirrhosis, and haemophilia, or to assess the haemorrhagic risk after thrombolytic therapy 47–50 . The assay has an intra-assay coefficient of variation of 5.15% which is similar to that reported for the thromboelastrography methods 41, 51 (3 to 6%), but higher than that for the optimised ECLT assay 13, 44 (0.7 to 2.6%).…”
Section: Discussionmentioning
confidence: 99%
“…Increased levels of tissue plasminogen activator and thrombin-activatable fibrinolysis inhibitors are also found to associate with severe clinical outcomes in hemophilia. 41 Owing to rarity of the disease and the exorbitant treatment costs, prophylactic management of moderate and severe HB with plasma-derived or recombinant FIX concentrates is a major challenge in the developing countries. Identification of factors modulating phenotypic heterogeneity may prove beneficial in management of such cases and will open new avenues in the treatment of HB.…”
Section: Discussionmentioning
confidence: 99%
“…Several retrospective studies have looked at the effect of coinheritance of prothrombotic mutations, with contradictory results. 6,9,[14][15][16][17][18][19][20][21][22][23][24][25] Some studies have found that severe hemophiliacs carrying a prothrombotic mutation have a milder phenotype characterized by older age at diagnosis, 25 older age at first bleed, 15,17,26 lower annual bleeding frequency, and less arthropathy. 21,22 In contrast, other studies failed to find significant differences in severity of disease attributable to the presence of a prothrombotic mutation.…”
Section: Discussionmentioning
confidence: 99%